Pengembangan Multimedia Interaktif Adobe FlashÂ® pada Pembelajaran Tematik Integratif Berbasis Scientific Approach Subtema Keindahan Alam Negeriku - Pangestika, Rintis Rizkia (KEGURU "Jurnal Ilmu Pendidikan Dasar", 2018)
This research aims to: (1) develop Adobe FlashÂ® -based interactive multimedia for scientific approach-based integrated thematic instruction on the sub-theme of âKeindahan Alam Negerikuâ for grade-IV students of SD Negeri Serayu, and (2) determine the effectiveness of the Adobe FlashÂ® -based interactive multimedia for scientific approach-based integrated thematic instruction on the sub-theme of âKeindahan Alam Negerikuâ for grade-IV students of SD Negeri Serayu. This research and development employed steps developed by Borg & Gall. They included: (1) researching and collecting data; (2) planning; (3) developing a draft product; (4) conducting the initial field trial; (5) revising the results of the field trial; (6) conducting the field trial; (7) revising the product resulted from the field trial; (8) trying out the field implementation; (9) conducting final product revision; and (10) Disemination. The findings suggest that the Adobe FlashÂ® -based interactive multimedia for scientific approach-based integrated thematic instruction on the sub-theme of âKeindahan Alam Negerikuâ for grade-IV students of SD Negeri Serayu fall under the âproper for useâ and âeffectiveâ categories.